Problem based learning berpendekatan Teaching at the Right Level (TaRL) untuk meningkatkan kemampuan menyelesaikan soal cerita pada materi vektor kelas XI SMA - Azizah, Qistin; Sudarsono, Agus; Sutarto, Hery (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2024)
The aim of this research is to improve students’ math story problem solving ability in class XI-F1 of SMA Negeri 13 Semarang through the implementation of Problem Based Learning (PBL) model with Teaching at the Right Level (TaRL) approach. The type of this research is classroom action research with research subjects of 36 students in class XI-F1 of SMA Negeri 13 Semarang. The data collection techniques used are test, observation and documentation. This research was carried out in 2 cycles. Before conducting classroom research, an initial test is carried out to determine students’ math story problem solving ability. From the initial test results, data was obtained that the average value of the test was 70.00 and the percentage of students’ test completion was only 41.67%. In cycle I the average score of students’ math story problem solving ability increased to 77.58 and the percentage of students' test completion was 66.67%. In cycle II the average value of students’ math story problem solving ability was 83.14 and the percentage of students’ test completion was 83,33%. Thus, it can be concluded that the implementation of PBL model with TaRL approach can improve students’ math story problem solving ability.